Electrophoretic and Other Properties of Bacteriophage Qβ: the Effect of a Variable Number of Read-Through Proteins - Radloff, Roger J. (1973)
When subjected to electrophoresis in polyacrylamide gels, the virions of wild-type Qβ bacteriophage are found in a single, major, anomalously wide band. With Qβ mutant 27-2, this wide band is replaced by a set of narrow, well-defined bands. The most rapidly migrating band of the mutant, comprising less than 10% of the total, contains defective virions. These virions have sedimentation coefficients ranging from 70 to 100% of the bulk of the unfractionated mutant, they contain no read-through protein (protein IIb), and they are deficient in maturation protein and contain fragmented RNA. The second band, comprising less than 3% of the total virus, has not been well characterized. The virions in the remaining electrophoretic bands are infective. Their distribution into bands is believed due to differences in their effective volume resulting from differences in their content of protein IIb. The most rapidly migrating band of this series contains virions with a few molecules of IIb protein, whereas the more slowly migrating bands contain virions with a larger number of IIb molecules. The adjacent bands in the series contain virions which differ by approximately three IIb molecules. Wild-type Qβ virus is similar to the mutant in that the more slowly migrating virions contain more protein IIb than the more rapidly migrating virions. Their failure to resolve into distinct bands upon electrophoresis is believed due to a less restricted packing of protein IIb into their virions. Both wild-type Qβ and mutant 27-2 also have 1 to 5% of the virions in the form of dimers which migrate with approximately one-half the mobility of the respective monomer forms. When the average amount of IIb per virion is increased by growth of the virus in a UGA suppressor strain, the electrophoretic pattern is altered. In the case of wild-type Qβ, the single band is wider, whereas with Qβ mutant 27-2 there occurs an increased number of partially resolved narrow bands. We suggest that the structural feature responsible for the difference in electrophoretic pattern between mutant 27-2 and wild-type Qβ is the mode of IIb packing in the virions. In the mutant, the IIb proteins are found in the virions only in multiples of three, whereas wild-type virions may differ by only a single IIb protein.